Powerchord: Towards Ambient Appliance-Level Electricity Use Feedback through Real-Time Sonification - Lockton, Dan; Bowden, Flora; Brass, Clare; Gheerawo, Rama (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
Feedback on energy use mainly uses visual, numerical interfaces. This paper introduces an alternative: energy sonification, turning real-time electricity use data from appliances into ambient sound. Powerchord, a work in progress prototype developed through co-creation with householders, is detailed.